2010
DOI: 10.1097/rct.0b013e3181e359c2
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Multiphase Time-Resolved Low-Dose Contrast-Enhanced Magnetic Resonance Angiography Using TWIST on a 32-Channel Coil at 3 T

Abstract: Time-resolved CE-MRA performed at 3 T with a 32-channel volume coil can be improved using the high-relaxivity agent gadobenate dimeglumine, which increases quality and quantity of vessel enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In recent investigations with a more technical focus, multiphase 3D-Gd-MRA has been shown advantageous in several respects [45]. It is also shown that Time-resolved CE-MRA performed at 3 T with a 32-channel volume coil can be improved using the high-relaxivity agent, which increases quality and quantity of vessel enhancement (Figure 3 courtesy) [46]. www.intechopen.com Fig.…”
Section: Magnetic Resonance Angiography Of the Abdomen And Pelvic Artmentioning
confidence: 97%
“…In recent investigations with a more technical focus, multiphase 3D-Gd-MRA has been shown advantageous in several respects [45]. It is also shown that Time-resolved CE-MRA performed at 3 T with a 32-channel volume coil can be improved using the high-relaxivity agent, which increases quality and quantity of vessel enhancement (Figure 3 courtesy) [46]. www.intechopen.com Fig.…”
Section: Magnetic Resonance Angiography Of the Abdomen And Pelvic Artmentioning
confidence: 97%
“…Furthermore, assessment of Gdbased contrast agents with higher relaxivity as well as imaging at 3T could be warranted as possible ways to reduce the total amount of contrast agent injected, particularly in patients at risk for developing NSF. [17][18][19][20] In conclusion, consecutive acquisition of TCMRA and PWI using a supplementary injection of a Gdbased contrast agent can facilitate preoperative diŠerential diagnosis in patients with suspected brain metastasis. This method also increases the number and conspicuity of lesions detected in patients with suspected metastatic disease to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…CMR-CENTRA is a dynamic approach to contrastenhanced angiography that involves rapid sequential imaging of an anatomic volume during the luminal transit of a contrast bolus (7,8). CMR-CENTRA involves the use of a T1-weighted gradient echo sequence with a short repetition-time (TR) to allow repeated imaging at a temporal resolution of less than 2 seconds per frame (14). The potential value of CMR-CENTRA in clinical practice is to permit continuous imaging throughout the arterial and venous phases of the contrast enhancement (7,8,14).…”
Section: Discussionmentioning
confidence: 99%
“…CMR-CENTRA involves the use of a T1-weighted gradient echo sequence with a short repetition-time (TR) to allow repeated imaging at a temporal resolution of less than 2 seconds per frame (14). The potential value of CMR-CENTRA in clinical practice is to permit continuous imaging throughout the arterial and venous phases of the contrast enhancement (7,8,14). In the present study, we required a total of 5 seconds to complete a single CMR-CENTRA examination covering the entire heart.…”
Section: Discussionmentioning
confidence: 99%